The secreted FolAsp aspartic protease facilitates the virulence of Fusarium oxysporum f. sp. lycopersici - Wang, Chenyang; Zheng, Yaning; Liu, Zhishan; Qian, Yongpan; Li, Yue; Yang, Limei; Liu, Sihui; Liang, Wenxing; Li, Jingtao (Frontiers in Microbiology, 2023)
Pathogens utilize secretory effectors to manipulate plant defense. Fusarium oxysporum f. sp. lycopersici (Fol) is the causal agent of Fusarium wilt disease in tomatoes. We previously identified 32 secreted effector candidates by LC-MS analysis. In this study, we functionally identified one of the secreted proteins, FolAsp, which belongs to the aspartic proteases (Asp) family. The FolAsp was upregulated with host root specifically induction. Its N-terminal 1–19 amino acids performed the secretion activity in the yeast system, which supported its secretion in Fol. Phenotypically, the growth and conidia production of the FolAsp deletion mutants were not changed; however, the mutants displayed significantly reduced virulence to the host tomato. Further study revealed the FolAsp was localized at the apoplast and inhibited INF1-induced cell death in planta. Meanwhile, FolAsp could inhibit flg22-mediated ROS burst. Furthermore, FolAsp displayed protease activity on host protein, and overexpression of FolAsp in Fol enhanced pathogen virulence. These results considerably extend our understanding of pathogens utilizing secreted protease to inhibit plant defense and promote its virulence, which provides potential applications for tomato improvement against disease as the new drug target.